Analysis of Social Marketing for Anti-Corruption Campaign: Case Study of Film “Kita Versus Korupsi” - Rosidah Rosidah (Bina Nusantara University, 2012)
The paper aims to explain the application of commercial marketing theory in a social marketing campaign. This study derives from secondary sources have been conducted, including previous researches and published articles. The writer finds yhat the theory of marketing mix has been used to study the film proposition. Furthermore, another “P”, namely Partnership, and segmentation has also been added to the campaign. The marketer has applied the commercial marketing approach in the film, as one of the campaigns for anti-corruption in Indonesia, to ensure that the campaign will be effectively delivered for the target audience. This finding can serve as a guideline for best practices in social marketing campaign for other sector or mission. In addition, the paper doesn’t aim to evaluate the effectiveness of the film as a social marketing campaign. It just wants to analyze the application of commercial sector marketing that applied in the film.